A boundary element method for a class of elliptic boundary value problems of functionally graded media. (November 2017) - Salam, Nasaruddin; Haddade, Amiruddin; Clements, David L.; Azis, Moh. Ivan
Abstract: A Boundary Element Method (BEM) is derived for obtaining solutions to a class of elliptic boundary value problems (BVPs) of functionally graded media (FGM). Some particular examples are considered to illustrate the application of the BEM.